A Privacy Enhanced Authentication Scheme for Telecare Medical Information Systems - Jiang, Qi; Ma, Jianfeng; Ma, Zhuo; Li, Guangsong (Journal of medical systems, 2013)
The telecare medical information system (TMIS) aims to establish telecare services and enable the public to access medical services or medical information at remote sites. Authentication and key agreement is essential to ensure data integrity, confidentiality, and availability for TMIS. Most recently, Chen et al. proposed an efficient and secure dynamic ID-based authentication scheme for TMIS, and claimed that their scheme achieves user anonymity. However, we observe that Chen et al.’s scheme achieves neither anonymity nor untraceability, and is subject to the identity guessing attack and tracking attack. In order to protect user privacy, we propose an enhanced authentication scheme which achieves user anonymity and untraceablity. It is a secure and efficient authentication scheme with user privacy preservation which is practical for TMIS.